Effects of diesel–Calophylluminophyllum biodiesel–propyl alcohol blends on performance, emissions, and combustion of diesel engine. Issue 5 (26th March 2022) - Nagpure, Anant G.; Chavan, Supriya B.; Rathod, Walmik S.
Abstract: The present experimental work aims to study the effects of higher alcohol with diesel– Calophyllum inophyllum biodiesel on diesel engine characteristics. The higher alcohol used for the investigation was propyl alcohol. Three samples were prepared with a diesel–biodiesel blend (B20) at 6%, 12%, and 18% concentration by volume of propyl alcohol (B20P6, B20P12, and B20P18). Tests were carried out on a single‐cylinder, four‐stroke diesel engine with varying loads and compression ratio. At higher compression ratios, the modified blends of propyl alcohol reported better efficiencies compared to diesel. Blend B20P12 has a 1.6% higher average brake thermal efficiency than diesel. For all blends, the brake specific fuel consumptions (BSFCs) were found to be increased in comparison to diesel. The blends B20P6 and B20P12 reported 12.8% and 13.8% higher average BSFCs than those of diesel. The blends B20P6 and B20P12 reported 15.7% and 29.5% less carbon monoxide emissions than diesel, respectively. A decrease of up to 4.6% in hydrocarbon emissions was also reported with propyl alcohol blends. Along with a reduction in nitrogen oxide emissions, propyl alcohol blends also reported lower peak cylinder pressure and a lower heat release rate compared to diesel. At a higher compression ratio, increased engine knock was observed with a higher amount of propyl alcohol. The experimental evaluation concluded that a 12% concentration by volume of propyl alcohol is the optimum value of the additive in the diesel– C. inophyllum biodiesel blend.